2016
DOI: 10.1039/c6ta01398h
|View full text |Cite
|
Sign up to set email alerts
|

A conductive polymer coated MoO3anode enables an Al-ion capacitor with high performance

Abstract: The feasibility of assembling an Al-ion capacitor with good electrochemical performance is demonstrated. Preliminary results indicate that the fabricated Al-ion capacitor could reversibly cycle in the voltage region of 0–1.5 V and display intriguing performances with an energy density of 30 W h kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 65 publications
3
69
0
Order By: Relevance
“…The presence of Cd +2 peak in Figure S1b confirmed the adsorption of Cd +2 onto the MoO 3 /Ppy surface. Elemental mapping of MoO 3 /Ppy (Figure S1c) and MoO 3 /Ppy‐Cd (Figure S1d) confirmed the presence of Mo, O, N, C, and Cd . TEM micrograph of MoO 3 /Ppy nanocomposite (Figure a) suggested that MoO 3 nanoparticles were randomly distributed into irregular chainlike structure of Ppy matrix .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The presence of Cd +2 peak in Figure S1b confirmed the adsorption of Cd +2 onto the MoO 3 /Ppy surface. Elemental mapping of MoO 3 /Ppy (Figure S1c) and MoO 3 /Ppy‐Cd (Figure S1d) confirmed the presence of Mo, O, N, C, and Cd . TEM micrograph of MoO 3 /Ppy nanocomposite (Figure a) suggested that MoO 3 nanoparticles were randomly distributed into irregular chainlike structure of Ppy matrix .…”
Section: Resultsmentioning
confidence: 81%
“…It was inferred from Figure S12 that intraparticle diffusion mechanism was not solely controlling adsorption kinetics as the plot did not pass through the origin. The higher values of C i for Cd +2 (24)(25)(26)(27)(28) and NB (81-87) suggested greater effect of external surface on adsorption mechanism. 65…”
Section: Dubinin-radushkevich Isothermmentioning
confidence: 96%
“…[114] A specific capacitance of 693 F g À 1 has been demonstrated in the voltage range of À 0.4 to 0.2 V (vs. SCE) under the current density of 1 A g À 1 . [114] A specific capacitance of 693 F g À 1 has been demonstrated in the voltage range of À 0.4 to 0.2 V (vs. SCE) under the current density of 1 A g À 1 .…”
Section: Systemmentioning
confidence: 94%
“…Recently, researchers also investigated Al storage behavior of the MoO 3 @PPy nanotube in 0.5 mol/L Al 2 (SO 4 ) 3 aqueous electrolyte. [114] A specific capacitance of 693 F g À 1 has been demonstrated in the voltage range of À 0.4 to 0.2 V (vs. SCE) under the current density of 1 A g À 1 . Ex-situ XRD, EDX, and elemental mapping further confirm the reversible intercalation/deintercalation of Al 3 + into/from MoO 3 .…”
Section: Systemmentioning
confidence: 94%
“…Combination with a lithium-ion intercalation negative electrode has been called Li-ion supercapacitor [92]. Recently, sodium-ion capacitors and aluminum-ion capacitors [93,94] as well as alternative concepts like thermally chargeable SCs have been proposed [95].…”
Section: Perspectivesmentioning
confidence: 99%